Familial Occurrence of Mycoplasma-induced Rash and Mucositis: A Case Report of Two Siblings - Roja Aepala; Satyanarayana Kavali; Srividya Devarakonda; Nikhil Dasari; Sai Goutham Manikyala (Journal of Clinical and Diagnostic Research)
Mycoplasma pneumoniae is a common pathogen responsible for respiratory infections, including community-acquired pneumonia, and up to 25% of patients develop extrapulmonary complications. Mycoplasma-Induced Rash and Mucositis (MIRM) is a recently identified clinical entity typically preceded by pneumonia-like symptoms such as fever and cough. The differential diagnoses for MIRM include Erythema Multiforme (EM), Stevens-Johnson Syndrome (SJS), Herpetic gingivostomatitis, Kawasaki disease and Toxic Epidermal Necrolysis (TEN). This condition primarily affects children and adolescents, with a mean age of 12 years and shows a male predominance. The authors report a rare occurrence of MIRM in two siblings, underscoring the condition’s rarity and clinical importance. The combination of prominent mucosal involvement at two sites, with sparse cutaneous findings, preceded by a prodrome of respiratory symptoms and the absence of a drug history, raised suspicion of Mycoplasma infection, which was confirmed by positive Mycoplasma IgM antibodies. Both siblings recovered well with a macrolide antibiotic and a short course of corticosteroids. While sporadic cases of MIRM are reported, familial occurrences in siblings highlight a genetic or environmental predisposition. Early recognition is crucial, as demonstrated by its occurrence in siblings, where prompt diagnosis led to favourable outcomes. Increased awareness among physicians can aid in accurate diagnosis, appropriate management and effective counselling.